Efforts Of Guest Relations Officer Of Hotel Tentrem Semarang In Handling Guest Complaints - Mellarisca Nadya Nur Rosena; Andi Hallang Lewa (FKIP, Universitas Palangka Raya, 2023)
In the daily operation of a hotel, it is inevitable that guest complaints will occur. Even though all the facilities and services provided are up to standard, it is not uncommon for hotels to encounter obstacles or problems that cause guests to be disappointed and guests submit them in the form of complaints. With this complaint phenomenon, a hotel provides a complaint service that connects guests with the hotel as a complaint handling strategy. This section is the Guest Relations Officer, Guest Relations is responsible for complaints submitted by guests and ensures that the service that guests receive during their stay is the best service. The author conducts research on Guest Relations efforts in handling complaints that occur at hotels. Because the Guest Relations Officer is tasked with handling complaints, a complaint handling system is needed that is systematically arranged. As an effort to handle complaints, a standard for handling complaints has been established. This standard is a benchmark for a hotel in providing Guest Relations services for guests. This study uses a qualitative descriptive research method. To obtain the data needed for writing this research using four methods, namely interviews, observation, documentation, and literature study so as to obtain accurate data. The data obtained is arranged in a research result that will be used as the author's final project. From the results of research conducted by the authors found that the handling of complaints carried out by the Guest Relations Officer at Hotel Tentrem Semarang went well so that complaints that occurred could be resolved properly. In addition to handling complaints, the authors also found that the Guest Relations Officer was also in charge of handling VIP guests, where these VIP guests were important people or members of the government. The results of this study indicate that the Guest Relations Officer is very influential in the service of a hotel, because listening to guest complaints and dealing with complaints can maintain guest confidence in the services provided by the hotel.